The Criminalization of Islamic Discourse in the Case of the Ar-Risalah Bulletin in Yogyakarta, 1983-1986 - Luthfiyadin Rizqi; Muhammad Wildan (Nur Science Institute, 2026)
This article examines the criminalization of Islamic discourse in the case of the Ar-Risalah Bulletin in Yogyakarta from 1983 to 1986. The study focuses on the shift in Ar-Risalah’s position from a media outlet for youth outreach at the Jenderal Sudirman Mosque to a text that was called into question in New Order-era news coverage and legal proceedings. This research employs historical methods through the stages of heuristics, source criticism, interpretation, and historiography, using a sociology of religion approach as well as Lewis A. Coser’s theory of social conflict. The primary sources for this research consist of contemporary news reports from Kiblat, Tempo, Berita Yudha, and Kedaulatan Rakyat, as well as an interview with Nur Wahid, a historical source regarding the General Sudirman Mosque. The findings reveal that the criminalization of Ar-Risalah occurred through the labeling of the bulletin as a disseminator of false news, a catalyst for unrest, a subversive entity, and a threat to Pancasila. This article emphasizes that the discourse on Islamic politics during the New Order era was not only present through political parties or large organizations but also through local spaces such as mosques, newsletters, reading networks, and youth communities outside the formal political institutions that were strictly controlled by the state at that time. REFERENCES Coser, L. A. (1956). The functions of social conflict. Glencoe, IL: Free Press. Effendy, B. (2011). Islam dan negara: Transformasi gagasan dan praktik politik Islam di Indonesia. Jakarta: Democracy Project. Eickelman, D. F., & Anderson, J. W. (2003). Redefining Muslim publics. In D. F. Eickelman & J. W. Anderson (Eds.), New media in the Muslim world: The emerging public sphere (2nd ed.). Bloomington: Indiana University Press. Hill, D. T. (2011). Pers di masa Orde Baru (G. W. L. Soerjoatmodjo, Trans.). Jakarta: Yayasan Obor Indonesia. Kiprah “Anak-Anak Sudirman”: Gelapnya sebuah citra. (1983, 5-20 Desember). Kiblat, 31(14). Latif, Y. (2012). Inteligensia Muslim dan kuasa: Genealogi inteligensia Muslim Indonesia abad ke-20.Jakarta: Democracy Project. Lawan, E. C. G. (2019). Pasal 14 dan Pasal 15 Undang-Undang Nomor 1 Tahun 1946 tentang Peraturan Hukum Pidana sebagai dasar penuntutan perbuatan menyiarkan kabar bohong (hoax). Lex Crimen, 8(5). Margiyono. (2009). Membangun benteng kebebasan: Seri reformasi kebijakan media. Jakarta: Aliansi Jurnalis Independen Indonesia. Mujiburrahman. (2007). Indonesian Muslims in the public sphere: A review of several studies. Journal of Indonesian Islam, 1(2), 356-378 DOI:10.15642/JIIS.2007.1.2.356-378. Pengadilan Ar Risalah: Surat dari “Bumi Allah”. (1985, 26 Oktober). Tempo, 15(35). Pengadilan subversi: Irfan, ingin dihukum mati. (1986, 22 Februari). Tempo, 15(52). Pengedar Bulletin Al-Risalah dituntut 8 tahun penjara. (1986, 10 Januari). Berita Yudha. Prayogi, A. (2019). Masuk dan berkembangnya Gerakan Tarbiyah, studi kasus: Gerakan Dakwah Kampus di Institut Teknologi Bandung (ITB) 1983-1998. SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 1(1), 45-57. DOI:10.31540/sdg.v1i1.204 Sopyan, I. (2014). Dari dakwah normatif ke dakwah transformatif: Dinamika kaum muda Masjid Syuhada Yogyakarta, 1980-an Skripsi, UIN Sunan Kalijaga Yogyakarta. Syamsuddin, M., & Fatkhan, M. (2010). Dinamika Islam pada masa Orde Baru. Jurnal Dakwah, 11(2), 145-146. https://ejournal.uin-suka.ac.id/dakwah/jurnaldakwah/article/view/2010.11203 Solahudin. (2011). NII sampai JI: Salafy jihadisme Indonesia. Depok: Komunitas Bambu. Terbukti edarkan Bulletin “Al Ikhwan”: Divonis 6 tahun, minta hukuman mati. (1986, 3 Februari). Kedaulatan Rakyat. Terdakwa pengedar “Ar Risalah”: Tuntutan delapan tahun hal yang berlebihan. (1986, 18 Januari). Kedaulatan Rakyat. Van Bruinessen, M. (2013). Rakyat kecil, Islam, dan politik (F. Wajidi & R. Iffati, Trans). Yogyakarta: Gading. Wahid, N. (2026). Wawancara oleh penulis pada 20 Mei 2026